Facile Hydrothermal Synthesis of MnWO4 Nanorods for Non‐Enzymatic Glucose Sensing and Supercapacitor Properties with Insights from Density Functional Theory Simulations. Issue 20 (18th July 2017) - Naik, Kusha Kumar; Gangan, Abhijeet Sadashiv; Pathak, Alok; Chakraborty, Brahmananda; Nayak, Saroj K.; Rout, Chandra Sekhar
Abstract: Here we report a facile and novel hydrothermal method to grow MnWO4 nanorods and their electrochemical glucose sensing and supercapacitor properties have been investigated. MnWO4 nanorods exhibited good glucose sensing performance with sensitivity of 13.7 μAμM −1 cm −2 in the 5–110 μM linear range and specific capacitance of 199 F/g at 2 mV/s and 256.41 F/g at 0.4 A/g. First principles simulations have also been carried out to qualitatively support our experimental observations by investigating the bonding and charge transfer mechanism of glucose on MnWO4 through demonstration of Partial Density of States and charge density distributions. Large Density of States near Fermi level and empty d states around 2 eV above Fermi level of Mn d orbital qualify MnWO4 as communicating media to transfer the charge from glucose by participating in the redox reactions. Insight into the electronic structure reveals that there is charge transfer from oxygen p orbital of glucose to d orbital of Mn. Also, the quantum capacitance of MnWO4 electrodes has been presented to justify its supercapacitor performance. The maximum quantum capacitance of 762 μF/cm 2 is obtained which is mostly contributed by the d electrons of Mn. Our experimental data and theoretical insight strongly infer that MnWO4 has the potential to be tailored as efficient and high‐performance glucose sensing and energy storage devices. Abstract : MnWO4 nanorods exhibited good glucose sensing performance with sensitivity of 13.7 μAμM −1 cm −2 in the 5–110 μM linear range with specific capacitance of 199 F/g at 2 mV/s and 256.41 F/g at 0.4 A/g. First principles simulations have also been carried out to qualitatively support our experimental observations by investigating the bonding and charge transfer mechanism.